THE CONCEPT OF TOLERANCE FROM LINGUISTIC AND CULTURAL PERSPECTIVES - Isroilova Ugiloy Isroil kizi (Bright Mind Publishing, 2025)
This article explores the concept of tolerance from linguistic and cultural perspectives, focusing on its semantic development, sociocultural interpretations, and functions in various types of discourse. Recognized globally as a fundamental value in promoting peaceful coexistence and intercultural communication, tolerance takes on different meanings depending on cultural and historical contexts. This study examines how the concept is expressed in language, how it functions in political, educational, and interpersonal communication, and how it reflects broader cultural ideologies. Through discourse analysis and cross-cultural comparison, the paper emphasizes the need for a context-sensitive understanding of tolerance, highlighting its role in shaping social harmony and mutual respect in diverse societies.
Keywords: Tolerance, discourse, cultural values, pragmatics, intercultural communication, linguocultural concept.